Impact of AI-Based Tools on Writing Skills - Ziar, Pohanyar Qyamudin (Journal of Research in Education, 2025)
The increasing presence of artificial intelligence (AI) in education has led to the widespread use of AI writing assistants like Grammarly, QuillBot, and GPT-based tools. These tools promise to enhance writing quality by improving grammar, style, and clarity. However, their effects on long-term writing skills, particularly in academic settings, remain a topic of concern. This study investigates the impact of AI writing assistants on the writing skills of 100 English Language and Literature students at Kabul University. As their writing teacher, I conducted this research using a structured questionnaire to collect data about students’ usage patterns, experiences, and perceptions of AI writing assistants. The results show that while students benefit from AI tools in terms of grammar and productivity, many express concerns about over-reliance and reduced critical thinking in writing. This research provides valuable insights into the role of AI in academic writing and offers recommendations for integrating AI tools without compromising skill development.